Congenital Presentation of a Solitary Superficial Angiomyxoma in the Parotid Region Masquerading as Parotid Tumor - Shailaja SHUKLA; Shivali SEHGAL; Pawani PRABHAT; Khushboo DEWAN (Federation of Turkish Pathology Societies, 2018)
Superficial angiomyxoma is a rare cutaneous and benign lesion. We present a case of congenital presentation of a superficial angiomyxoma in the parotid region in a 9-year- old female that was misdiagnosed as a parotid tumor. Appropriate diagnosis is important since such lesions have a good prognosis and rarely affect deeper structures. Possibility of superficial angiomyxoma should be kept in mind in the differential diagnosis of lesions of the parotid region.